Youth Awareness Level towards Sustainable Development Goals (SDGs) in Greater Kuala Lumpur - Zul Ilham; A’syara Kamal; Wan Abd Al Qadr Imad Wan-Mohtar; Adi Ainurzaman Jamaludin (Pusbindiklatren Bappenas, 2021)
In 2015, the United Nations initiated the Sustainable development goals (SDGs) to address the global changes while ensuring better and sustainable actions for the future. Among Asian countries, Malaysia has also made an effort to integrate the SDGs into its national development plan. In this study, the awareness level of youth from high schools in Greater Kuala Lumpur towards Sustainable Development Goals has been assessed through questionnaires with 60 questions given to 421 respondents. Sufficient levels of feedbacks for the whole population were acquired (Confidence level: 95%, Margin of error: 5%). Five schools were selected and grouped into 3 types: high-performance school (national merit of excellence), cluster school (state level merit of excellence), and daily school (normal achievement). The results of the Spearman Rho correlation showed a significant but weak relationship [r= 0.435] between attitude and practice for all schools. Interestingly, the statistical test showed a negligible relationship between knowledge and attitude, and knowledge and practice, indicating a low attitude to practice SDGs amongst youth although equipped with adequate knowledge. The study also found that high-performance schools showed the highest score for all knowledge, attitude, and practice.